Fulminant presentation of autoimmune hepatitis. Issue 6 (June 2015) - Mendizabal, Manuel; Marciano, Sebastián; Videla, María G.; Anders, Margarita; Zerega, Alina; Balderramo, Domingo C.; Tisi Baña, Matías R.; Barrabino, Martín; Gil, Octavio; Mastai, Ricardo; Yantorno, Silvina; Gadano, Adrián; et al.
<x xml:space="preserve">Abstract</x> Background and aims Classical features of autoimmune hepatitis (AIH) may be altered during the abrupt onset of the disease. Corticosteroid therapy can be life-saving, but its use in the fulminant presentation of AIH (F-AIH) remains controversial. We aimed to assess the clinical features of patients with F-AIH and to describe the role of corticosteroids in this population. Patients and methods We retrospectively analyzed 154 adult patients with fulminant hepatic failure who were admitted to six liver transplantation (LT) programs. The AIH simplified criteria were used to identify patients with F-AIH. Results We identified 40 (26%) patients with F-AIH. Compared with other etiologies, patients with F-AIH presented a longer interval from jaundice to encephalopathy (26 vs. 16 days, P=0.02) and a lower Model for End-Stage Liver Disease (MELD) score on admission (29 vs. 33, P=0.002). Overall, 25 (62%) patients with F-AIH underwent LT, eight (20%) patients survived, and seven (18%) died without LT. Seventeen patients received corticosteroids therapy, of whom seven (41%) survived without LT. Among the treated patients, higher MELD score and encephalopathy grade of 3 or more were associated significantly with corticosteroid failure. Conclusion Patients with F-AIH have a more indolent presentation compared with the non-F-AIH population. Altogether, only eight (20%) patients presenting with F-AIH survived without LT. A subset of patients with F-AIH and an initial MELD score less than 27 and low-grade hepatic encephalopathy might benefit from administration of corticosteroids.